The impact of online design thinking-based learning on entrepreneurial intention: The case of vocational college - Issariya Woraphiphat; Pattama Roopsuwankun (Journal of Innovation and Entrepreneurship, 2023)
Entrepreneurial intention is fundamental to decision-making and the behaviors needed to become entrepreneurs, with subsequent effects on economic development. However, the COVID-19 pandemic calls for a novel approach to teaching entrepreneurship owing to the shift to online learning. The current study explores entrepreneurial intention and the satisfaction derived from the entrepreneurship education program. In particular, we offer a framework that explains students' satisfaction and entrepreneurial intention by integrating the theory of planned behavior with design thinking-based entrepreneurship courses, peer interactions, and speaker interactions. The entrepreneurship education program was for vocational college students located in Southeast Asia. The online questionnaire was distributed to participants (N = 263, MAGE = 18.64) at the end of the online entrepreneurship education program. The model was tested using a structural equation model analysis. Attitude, subject norm, and satisfaction were found to predict higher entrepreneurial intention among vocational college students. Moreover, design thinking-based entrepreneurship courses, peer interaction, and speaker interaction indirectly affect entrepreneurial intention through satisfaction. This research extends the literature on entrepreneurship education by proposing a novel learning approach, that is, the online design thinking-based learning approach, which could be applied to entrepreneurship education programs to enhance students' entrepreneurial intention.
Keywords: 650; Design thinking; Entrepreneurial intention; Entrepreneurship education; Interaction; Online learning; Satisfaction; Theory of planned behavior